Corruption as a threat to national security - Antonova, Liudmyla; Abdullayev, Vahif (Public Administration and Regional Development, 2021)
The article substantiates the need to overcome the anti-social phenomenon of corruption and the relevance of its study as a factor threatening national security. A comprehensive analysis of the latest case studies and publications. The essence of such multicomponent concepts as "corruption", "national security of Ukraine", "national interests of Ukraine", "threats to the national security of Ukraine", "anti-corruption policy", "anti-corruption strategy" is substantially revealed. The components of national security of Ukraine, its main objects are indicated. The main institutional threats to the national security of modern Ukraine have been identified. The phenomenon of corruption as a factor of threat to the national security of modern Ukraine is highlighted and proposals are made to eliminate corruption in the domestic national security system. The causes and conditions of the origin, existence and spread of modern corruption have been clarified. Corruption as a modern transnational and cross-border phenomenon is revealed. The globalization phenomenon of corruption from the standpoint of transnationalism is characterized. The characteristic features of the phenomenon of corruption in modern Ukraine have been clarified. The mission and purpose of modern anti-corruption policy have been defined. A systematic analysis of draft anti-corruption strategies of Ukraine was carried out. Relevant provisions to a probable national anti-corruption strategy are proposed. Practical proposals for reducing the level of corruption in domestic public authorities are provided. The connection between the existence of corruption and the presence of the human factor is argued. The role and significance of corruption in the issues of interstate interaction and cooperation are determined. Theoretical and practical substantiation of the urgent need to improve and develop mechanisms to prevent and combat corruption, taking into account foreign experience at the present stage of development of the Ukrainian state. In order to introduce effective mechanisms for the implementation of domestic anti-corruption policy, direct and institutional measures to combat corruption have been proposed. Perspective directions of further theoretical and practical research of the phenomenon of corruption as a factor of threat to national security are given.